(untitled) (Fiep Bulletin - online, 2024)
The present study aims to verify the practical applications of Manual Resistance Training (TRM). For this, an integrative bibliographic review was carried out, where there was a search for the portals of journals: CAPES, PUBMED, Scielo Brasil, LILACS, Google Scholar. In all, 66 results were found, however, after refinement, 11 articles were selected. It is concluded that the TRM has been efficient when applied to several groups, namely: elderly, adults, adolescents, children and athletes.